The prevalence of welfare state policies and gender socioeconomic inequality: A comparative analysis - Hadas Mandel; Moshe Semyonov (Luxembourg Income Study (LIS), 2003)
The present study examines the hypotheses that progressive welfare-state policies are likely to increase women's labor force participation, but at the same time to increase both occupational segregation and earning gaps between economically active men and women. Using data from 20 industrialized countries (obtained from the Luxembourg Income Study), we combine both individual-level and country-level variables into one data file. The country-level variables pertain to a series of family oriented policies enacted by the state, and to the size of the public welfare sector. The data are analyzed to estimate the net effects of welfare state policies on female labor force participation, occupational segregation, and gender earnings inequality across the 20 countries. The analysis lends firm support to the hypothesis that progressive welfare policies are associated with higher rates of female labor force participation and with higher rates of gender-based occupational segregation but only limited support to the hypothesis that welfare-policies are likely to decrease gender inequality in earnings. The direct and indirect effects of welfare-state policies on earnings inequality obtained from multilevel regression models are discussed and re-evaluated in light of sociological theory.
Keywords: 330; Sozialstaat; Sozialpolitik; Weibliche Arbeitskräfte; Lohnstruktur; OECD-Staaten; Geschlechterforschung